2023
DOI: 10.1371/journal.ppat.1011185
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus UL138 interaction with USP1 activates STAT1 in infection

Abstract: Innate immune responses are crucial for limiting virus infection. However, viruses often hijack our best defenses for viral objectives. Human Cytomegalovirus (HCMV) is a beta herpesvirus which establishes a life-long latent infection. Defining the virus-host interactions controlling latency and reactivation is vital to the control of viral disease risk posed by virus reactivation. We defined an interaction between UL138, a pro-latency HCMV gene, and the host deubiquitinating complex, UAF1-USP1. UAF1 is a scaff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…Furthermore, we and others have shown that latent viral gene products regulate components of the innate immune system 37,[39][40][41][42] which may also serve to counteract this additional function of MORC3.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we and others have shown that latent viral gene products regulate components of the innate immune system 37,[39][40][41][42] which may also serve to counteract this additional function of MORC3.…”
Section: Discussionmentioning
confidence: 87%
“…Whether the downregulation of MORC3 in the context of cellular differentiation is less clear—it is not reported that differentiating myeloid cells spontaneously start expressing IFN‐beta so this may be a moot point in the context of viral reactivation. Furthermore, we and others have shown that latent viral gene products regulate components of the innate immune system 37,39–42 which may also serve to counteract this additional function of MORC3.…”
Section: Discussionmentioning
confidence: 89%
“…We were struck by the similarity between the WT and Δ UL138 STOP viral transcriptomes, given the replicative phenotype in CD34 + HPCs where the Δ UL138 STOP recombinant produces similar numbers of infectious progeny both prior to and following reactivation stimulus, demonstrative of a loss of latency ( 27, 29, 30, 40 ). To further explore this, we analyzed Δ UL138 STOP infection in vivo using humanized mice (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been discovered that USP1-associated factor 1 (UAF1) and ubiquitin-specific peptidase 1 (USP1) deubiquitinate the proteins FANCD2, FANCI, and PCNA to control DDR. The UAF1-USP1 association may be necessary for HCMV UL138 to control pSTAT1 for virus genomic latency, according to recent studies, raising the possibility that pSTAT may be an effector in virus infection-induced DNA damage [ 183 ].
Fig.
…”
Section: The Interactions Between Innate Immune Signaling Pathways An...mentioning
confidence: 99%